Challenges Facing Released Prisoners and People with Criminal Records: A Focus Group Approach. Issue 2 (3rd April 2017) - Jones, Mark; Coleman, Samantha; Leierer, Stephen
ABSTRACT: Three rounds of guided focus group sessions were held in 2014, with a total of 27 participants, all of whom had at some point within the past seven years been released from incarceration, with some serving short terms in local jails and others having been incarcerated for periods ranging from a few months to 8–10 years. The focus group sessions were held in a nonresidential facility in Charlotte, North Carolina that assists former inmates and other people with criminal records with transitioning or adjusting to the community. The intention was to discover barriers and challenges associated with reentering the community after a period of incarceration and/or living with the stigma of a criminal record. Various theoretical underpinnings are discussed.